Simultaneous transportation of multiple shelves by single mobile robot and passive docking mechanism - Yuta WAKABAYASHI; Jun KINUGAWA; Masaya KAMIOKA; Kazuhiro KOSUGE (Nihon Kikai Gakkai ronbunshu, 2021)
In logistics warehouses, Goods-to-Person systems (i.e., kitting transport systems) and workers work together in order to improve the efficiency of kitting (also called “picking”) tasks. On the other hand, in assembly factories that also require kitting tasks, Goods-to-Person systems have not yet been implemented. We propose a novel robot co-worker called Kitting Parts Delivery system (i.e., KitPaDY) to expedite work processes at assembly factories. Unlike existing Goods-to-Person systems that are designed to use a mobile robot to transfer a single shelf at a time, KitPaDY adopts a novel mechanism that enables a single mobile robot to transfer multiple shelves simultaneously. The mechanism is mounted on every shelf and does not need any power. Rather, it uses the drive of a mobile robot to group shelves together; this also simplifies the control of the mobile robot. Here, we describe the mechanism behind KitPaDY and the mobile robot’s motion. Furthermore, we conducted an experiment to gauge KitPaDY’s ability to simultaneously transport multiple shelves. Additionally, by comparing KitPaDY with existing transport systems for current kitting processes, we demonstrated our system’s efficacy in the simulations. The simulation results show that KitPaDY can reduce the required number of mobile robots by 75% compared to existing transport systems.